Pass-Through as an Economic Tool: Principles of Incidence under Imperfect Competition - Weyl, E. Glen; Fabinger, Michal (Journal of Political Economy, 2013)
We extend five principles of tax incidence under perfect competition to a general model of imperfect competition. The principles cover (1) the independence of physical and economic incidence, the (2) qualitative and (3) quantitative manner in which taxes are split between consumers and producers, (4) the determinants of tax pass-through, and (5) the integration of local incidence to determine the overall division of surplus. We show how these principles can be used to simplify and generalize the analysis of a range of economic questions such as the optimal procurement of new markets and the welfare effects of third-degree price discrimination.